Wide Sargasso Sea - Rhys J. Jean (London, Penguin Books, 1968)
Born into an oppressive, colonialist society, Creole heiress Antoinette Cosway meets a young Englishman who is drawn to her innocent sensuality and beauty. But soon after their marriage, rumors of madness in her family poison his mind against her. He forces Antoinette to conform to his rigid Victorian ideals.